Serum vitamin E concentrations at 1 year and risk of atopy, atopic dermatitis, wheezing, and asthma in childhood: the PASTURE study. Issue 1 (11th November 2013) - Nwaru, B. I.; Virtanen, S. M.; Alfthan, G.; Karvonen, A. M.; Genuneit, J.; Lauener, R. P.; Dalphin, J.‐C.; Hyvärinen, A.; Pfefferle, P.; Riedler, J.; Weber, J.; Roduit, C.; et al.
Abstract Background Prospective studies investigating the role of serum vitamin E concentrations during early life in the development of childhood allergies and asthma are limited. Objective To study the associations between serum vitamin E concentrations at first year of life and longitudinal development of atopy, atopic dermatitis, wheeze, and asthma up to 6 years of age. Methods The setting was the PASTURE study, a multicenter prospective birth cohort study in five European rural settings. Children of 1133 mothers recruited during pregnancy were followed from birth with measurement of serum vitamin E levels at year 1 and repeated assessments of serum immunoglobulin E antibodies (year 1, 4.5, 6), atopic dermatitis, wheezing symptoms, and asthma (year 1, 1.5, 2, 3, 4, 5, 6). Results At 6 years of age, 66% and 82% of the original 1133 subjects underwent blood test for IgE and answered the questionnaire, respectively. We did not observe any statistically significant associations between serum vitamin E concentrations at year 1 and the endpoints, but borderline inverse associations between alpha tocopherol and wheezing without cold (OR 0.45, 95% CI 0.19–1.09) and any wheezing symptom (OR 0.52, 95% CI 0.27–1.02). Conclusions Serum vitamin E concentrations at year 1 were not associated with allergies or asthma by 6 years of age. While further prospective studies with repeated assessments of vitamin E during early life may clarify its putative role in the development of the diseases, it is also possible that the antioxidant hypothesis in the development of allergies and asthma does not hold.